Strategi Guru dalam Mengatasi Rendahnya Minat Peserta Didik dalam Pembelajaran Seni Rupa Kelas IV Sekolah Dasar - Raharjo, Andika Budi; Setiawan, Deni (Universitas Muhammadiyah Magelang, 2026)
This study discusses the low learning interest of fourth-grade students in fine arts learning at SD Negeri 2 Banjarejo, which is characterized by a lack of enthusiasm and student participation. The purpose of this study is to describe teacher strategies in overcoming low learning interest, determine the condition of student learning interest, and identify the causal factors. This study uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving fourth-grade teachers and students. Data analysis was carried out using the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers implemented active learning strategies, the use of interesting media, project-based learning, and providing positive reinforcement. These strategies were able to increase student involvement and interest in learning in fine arts learning so that the learning process became more effective and enjoyable.